Experimental study on the effects of a moving sun patch on heating radiant slabs: The issue of occupants’ thermal comfort - Li, Tianying; Merabtine, Abdelatif; Lachi, Mohammed; Bennacer, Rachid; Kauffmann, Julien (Solar Energy, 2023)
In pursuit of a better indoor thermal environment, radiant heating systems have been widely employed in residential buildings. The effect of the sun patch on floor heating systems is increasingly attracting attention. However, the experimental study on the effect of a moving sun patch is often limited by weather conditions. This study proposes a method to simulate the moving sun patch by heating films in experiments and uses a thermal manikin to evaluate the indoor thermal comfort. The experiments were performed in Troyes, France, which belongs to a temperate oceanic climate. The obtained results show that a moving sun patch decreases the indoor thermal comfort from 1.5 to 1.1 away from comfortable in the case with 11.6% of window-to-wall ratio (WWR). Besides, concerning the overheating problems caused by the sun patch, two potential solutions are proposed. The indoor humidification solution could reduce air overheating duration by 74% in the case with 5.8% of WWR, and by 27% in the case with 11.6% of WWR, respectively. The solution with full return water could reduce the floor surface overheating duration by 40% and by 29%, respectively. In the future, the two solutions can be combined to alleviate the indoor overheating problems induced by the solar radiation.
Keywords: Floor heating system; Humidification; Sun patch; Thermal comfort; Thermal manikin